Perbandingan Metode Latihan Maraton Jarak Bertahap dan Hill Run Terhadap Peningkatan VO2max - Kemal Muamar Sidki; Gani Kardani; Ruli Sugiawardana; Muhammad Nurzaman (Jurnal Keolahragaan, 2023)
This study aims to compare the effectiveness of gradual distance marathon training and hill run methods on improving VO₂max in extracurricular soccer participants at SMKN 1 Kawali, Ciamis Regency.The research method used was an experiment with a Two-Group Pretest-Posttest Design. The sample consisted of 24 students selected through purposive sampling and divided into two treatment groups. VO₂max measurements were conducted using the Multi-Stage Fitness Test (MSFT). The normality test of the data yielded an Asymptotic Significance value of 0.200, indicating that the data were normally distributed. The homogeneity test resulted in an Asymp. Sig. value of 0.107, indicating that the variances between groups were homogeneous. The first and second hypothesis tests using a paired sample t-test on each group showed a significant increase in VO₂max with an Asymp. Sig. (2-tailed) value of 0.000. The third hypothesis test using ANOVA showed a significant difference between the two training methods with an Asymp. Sig. value of 0.000.The results of this study conclude that both the gradual marathon distance method and the hill run method are effective in increasing VO₂max, but there is a significant difference in effectiveness between the two. These findings contribute to more targeted physical training strategies for developing the aerobic capacity of teenage soccer players.